Anisotropic transport properties of tungsten disulfide. (15th March 2016) - Pisoni, Andrea; Jacimovic, Jacim; Gaál, Richard; Náfrádi, Bálint; Berger, Helmuth; Révay, Zsolt; Forró, László
Abstract: Single crystals of WS2 were prepared by chemical vapor transport method using sulfur as a transport agent. Measurements of electrical resistivity, Seebeck coefficient and thermal conductivity as a function of temperature, along the in-plane and the out-of-plane directions reveal distinct trends. In our interpretation these differences are mainly due to the different nature of the chemical bonding in the two directions and to the presence of impurity intercalates in between the planes. Graphical abstract: